From the Editor's Desk - Alvita Nathaniel (Grounded Theory Review: An International Journal, 2021)
I have been thinking about the value of modifiability as a criterion of classic grounded theory rigor. In June 2020, I wrote about the need for research, and especially grounded theory research focused on changing social processes. What I couldn’t foresee was that we were on the mere cusp of multi-year virulence and social upheaval. I wrote, “These are troubling days of pandemic illness, cultural upheaval, racial animus, international disruption, and political turmoil. . . . We are in uncharted territory. In response, particularly to Covid-19, structural and psychological social processes are changing. Education, family life, health care, work life, business, consumerism, sports, trade, entertainment, government institutions, and travel are all changing. People are assuming new roles or are adjusting their roles to fit new life circumstances. This is a time of great upheaval—a time particularly ripe for grounded theory research.” As a call for action, I urged grounded theorists and PhD students to turn aside from tired and over-studied phenomena and consider this wide-open opportunity to advance important knowledge. What I did not suspect at the time was that global society was at the mere beginning of a swirling maelstrom of change and that theories discovered in 2020 might need to be modified in order to be useful in the future.